Bone tumor mimickers: A pictorial essay - Mhuircheartaigh, Jennifer Ni; Lin, Yu-Ching; Wu, Jim S (Indian Journal of Radiology and Imaging, 2014)
Focal lesions in bone are very common and many of these lesions are not bone tumors. These bone tumor mimickers can include numerous normal anatomic variants and non-neoplastic processes. Many of these tumor mimickers can be left alone, while others can be due to a significant disease process. It is important for the radiologist and clinician to be aware of these bone tumor mimickers and understand the characteristic features which allow discrimination between them and true neoplasms in order to avoid unnecessary additional workup. Knowing which lesions to leave alone or which ones require workup can prevent misdiagnosis and reduce patient anxiety.
Keywords: Bone tumors; MRI artifacts; osteomyelitis; traumatic lesions; tumor mimickers